ENSINO MÉDIO ARTICULADO A EDUCAÇÃO PROFISSIONAL NO SESI-MA E SENAI-MA, MODALIDADE EJA - Monteiro, Raimundo Flor (2013)
This dissertation examines the articulation of high school with vocational education (EBEP - EJA) developed by SESI - MA - Social Service of Industry and Senai - MA - National Service of Industrial Learning. The study is linked to the State Line of Research and Education Management Research Group Policies Basic Education Program Graduate Education UFMA. The general objective that guided the development of the study was to analyze the EBEP - EJA in the form of Youth and Adults in concomitantly, technical course in mechanics, identifying the legal and institutional guidelines that guide the development of the proposal, analyze the skills professionals that guide the process of training, identify the expectations of students' education, meeting the demands of the market, and analyze the array of vocational training in the light of the reference matrix demanded by industrial firms that receive the graduates of the EJA EBEP SESI - MA and MA - SENAI Objectives of general and specific questions emerged about the theoretical training that shape the structure of training developed in the course analyzed. The construction of the theoretical framework that has underpinned the development of the study were the contributions of Frigotto, (2005), Ciavatta (2009), Ramos (2001), Oliveira (2005), Kuenzer (2007), among others, and documentary analysis of following documents: Constitution, LDBEN No. 9.394/96, Laws, Decrees and resolutions, and institutional frameworks CNI FIEMA, SESI and SENAI. Were used as research tools questionnaires, interview guide, applied to a sample of 28 pre- selected subjects among students, technical school, and the companies that receive the SENAI graduates of courses in addition to the in situ observations to broaden the information on the object searched. Through the confrontation between the provisions of legal documents and institutional data and information collected through survey instruments was possible to identify weaknesses and strengths in the process of articulation between high school and professional education which raises the intervention with a view to correcting the discrepancies in order to compromise the achievement of course objectives, given the gaps present in the technical training in mechanics, pointed out by the companies, which causes the distance between the training required and that which is effectively developed. Finally it is emphasized that the project EBEP - EJA comprises a training path that is relative to the demands of training presented by the industrialist labor market Maranhão, in such case, favors the development of the skills required to ensure employability of the graduates of the course.